Transgenic Medicago truncatula Plants That Accumulate Proline Display Enhanced Tolerance to Cadmium Stress - García de la Torre, Vanesa S.; Coba de la Peña, Teodoro; Lucas, M. Mercedes; Pueyo, José J. (Frontiers in Plant Science, 2022)
Cadmium (Cd) accumulation in agricultural soils constitutes a serious problem for crop yields and food safety. It is known that proline (Pro) can rapidly accumulate in plant tissues in response to abiotic stress. To analyze the potential protective effect of Pro accumulation against Cd toxicity, we compared the response to Cd stress of wild-type (WT) Medicago truncatula and a transgenic line that we had previously obtained and characterized (p18), which expressed the Δ1-pyrroline-5-carboxylate synthetase gene from Vigna aconitifolia (VaP5CS), and accumulated high Pro levels. Cadmium significantly reduced germination of WT seeds compared to p18 seeds, and seedling relative root growth, a valid indicator of metal tolerance, was significantly higher for p18 than WT seedlings. We analyzed the relative expression of genes related to Pro metabolism, phytochelatin biosynthesis. antioxidant machinery, and NADPH recycling, which are relevant mechanisms in the response to Cd stress. They presented differential expression in the seedlings of both genotypes both under control conditions and under Cd stress, suggesting that the Cd response mechanisms might be constitutively activated in the transgenic line. Pro accumulation promoted higher survival, enhanced growth performance, and minor nutrient imbalance in transgenic p18 plants compared to WT plants. These facts, together with the recorded gluthatione levels, lipid peroxidation and antioxidant enzyme activities strongly suggested that VaP5CS expression and Pro accumulation conferred enhanced Cd tolerance to M. truncatula p18 plants, which was likely mediated by changes in Pro metabolism, increased phytochelatin biosynthesis and a more efficient antioxidant response. Moreover, p18 roots accumulated significantly higher Cd amounts than WT roots, while Cd translocation to the aerial part was similar to WT plants, thus suggesting that high Pro levels increased not only Cd tolerance, but also Cd phytostabilization by rhizosequestration.